Factors Affecting Romantic Relationship in Lebanon - El Hage, Jad; Moussi, Joyce; Nohra, Dunya (Technium Social Sciences Journal, 2024)
The concepts of romance and love are rapidly evolving with new modalities of romantic relationships in Lebanon (civil marriage, cohabitation) along with a catastrophic economic crisis affecting the country since 2019, and being ranked among the top ten crises worldwide. This document represents a cross-sectional study investigating 585 Lebanese participants from different Lebanese regions randomly sampled using the snowball method. Besides, the Relationship dynamics scale (RDS) was used to evaluate vulnerability for conflicts in the context of romantic relationship and their correlates, with a very good internal consistency (Cronbach’s Alpha of 0.908) and an excellent validity (Factor analysis using Promax technique). The results are as follows: A higher vulnerability for conflicts in the context of amorous relations is associated with having a child or a partner with handicap or receiving an actual chronic treatment (personal, for children or for the partner), having 3 or more children and finally having high financial stressors. Moreover, this survey evaluated factors modulating financial burden and stress using the InCharge Financial Distress / Financial Well-Being (IFDFW) scale. The results showed that working only with day shifts schedule, being male, having physical activity of a minimum of 2.5 hours per week, having a partner working outside Lebanon, having an income in currency other than Lebanese Pound, and being married at an age above 30 years are associated with less stressful economic status. While on the other hand, having a history of chronic treatment (Personal, Partner or children) and being married before 18 years were correlated with high levels of economic stress.